Private Equity in Sub-Saharan Africa - Mate, Joseph (My University, 2011)
Private equity refers to the pooling of funds from investors for investment in private companies, as distinguished from publicly traded companies. The terms Private Equity and Venture Capital are often used interchangeably. Venture Capital is in fact a subset of Private Equity and refers to investments made for the start-up and early development of the business. Private equity as an asset class has taken on significant importance in emerging markets and in particular Sub- Saharan Africa because of its potential to be a positive contributor to economic development and unlock value in a business. However the dynamics of doing business in Sub-Saharan Africa differ greatly from a developed market. Emerging markets are characterised by minimal shareholder rights, limited regulatory and legal framework - which impacts negatively on the enforcement of contracts, poor accounting standards which in turn affect the quality of reporting, nascent capital markets and unstable political environments. Such conditions pose a considerable challenge for private equity in emerging markets and Sub-Saharan Africa in particular. The aim, therefore, of the study was to establish the success factors necessary for the establishment of a private equity fund in Sub-Saharan Africa - given the challenges associated with emerging markets. A representative cross-section of private equity firms were interviewed in order to gain an in depth understanding private equity in the region, its process, parties involved as well as the determinants of its success. The study employed the use of a small, purposely selected, non-random sample in order to achieve depth of understanding, as opposed to finding out what is generally true of the many, as in the positivist approach. Textual analysis was applied, whereby common themes were identified from the discussions and analysed further by relating back to the research propositions and relevant literature. Thus a set of basic heuristics can be established for private equity in Sub-Saharan Africa based on the findings of the study.
MBA - WBS
Keywords: Equity; Private equity; Venture capital